YIA 03-04 EPIGENETIC CHANGES AFTER ACUTE TREATMENT WITH ACUTE ANGIOTENSIN CONVERTING ENZYME INHIBITORS (ACEi). (September 2016) - De Vries, Nathan; Prestes, Priscilla; Rana, Indrajeet; Harrap, Stephen B.; Charchar, Fadi J.
Abstract : Objective: The 'legacy effect' of hypertension treatment is where short term treatment with blood pressure (BP) lowering drugs such as angiotensin converting enzyme inhibitors (ACEi) is followed by a persistent reduction in BP, reduced cardiovascular complications and increased lifespan. However, the involvement of epigenetics mechanisms remains unclear. DNA methylation is the binding of a methyl group to DNA which inhibits gene transcription. The aim of this study is to investigate DNA methylation changes after short term treatment with ACEi. Design and Method: Spontaneously hypertensive rats were treated with the ACEi perindopril for 48 hours at 6 weeks old. Average global DNA methylation was quantified in renal cortices from perindopril (n = 6) and vehicle-treated animals (n = 6) using the 5-mC ELISA Kit (Zymo Research, USA) which features a unique anti-5-methylcytosine monoclonal antibody that is both sensitive and specific for 5-mC. We also measured the expression of epigenetic regulators histone deacetylase 1 ( Hdac1 ), solute carrier family 16 member 3 (monocarboxylate transporter, Mct3 ) and DNA (cytosine-5-)-methyltransferase 1 ( Dnmt1 ) using quantitative PCR. Results: Global DNA methylation was reduced in the renal cortices of animals treated with ACEi (P < 0.05, Figure 1). Acute treatment with perindopril did not significantly change the renal expression of Hdac1, Dnmt1 and Mct3 (P > 0.05). Conclusions: Acute treatment by ACEi results in a reduction in global DNA methylation indicating that epigenetics may play an important role in the 'legacy effect'. Further investigation into which specific genes contribute to these changes and if longer course of treatment have a higher impact in the expression of such genes is important.